Pengaruh Komunikasi Interpersonal, Kestabilan Emosi dan Dukungan Sosial terhadap Employee Performance (Studi Kasus Bank Muamalat KC Medan Balaikota) - Vira Yuniar; Ahmad Perdana Indra (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis study aims to determine the effect of Interpersoonal Communication, Emotional Stability, and Social Support on Employee Performance at Bank Muamalat Medan Balaikota. The analytical method used is multiple regression analysis using SPSS 16.0 software. The sampling technique used is saturation sampling. The number of population in this study was 30 respondents. The results of this study indicate that interpersonal comunication and emotional stability have a positive and significant effect on employee performance, while social support has no effect on employee performance.Keyword : Interpersonal comunication, Emotional Stability, Social Support, Employee Performance